Green marketing strategies: environmentally friendly batik ecosystems in niche and mass market segments in Pekalongan - Natasya Putri Hardiahsyah; Inaya Sari Melati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Consumer awareness of environmental issues encourages batik MSMEs in Pekalongan to adopt green marketing strategies to support business sustainability. This study aims to analyze the implementation of green marketing strategies in two environmentally friendly batik ecosystems, namely the niche market and the mass market, and to map the interactions among actors within these ecosystems. A qualitative approach was employed through semi-structured interviews, field observations, literature review, and Social Network Analysis (SNA) to understand actor roles, marketing innovations, and distribution strategies. The results show that in the mass market segment, the success of green marketing is highly dependent on workers as the main actors who ensure consistency in quality, production, and the application of environmentally friendly principles, supported by government intervention and the use of digital technology. In contrast, in the niche market segment, sustainability is more strongly determined by business owners, communities, and market relationships that build the image of batik as an exclusive art product. These findings emphasize that green marketing strategies are most effective when implemented through collaboration among actors with co-creation of value and, and highlight the importance of strengthening worker capacity, innovation, and technology integration to enhance the competitiveness and sustainability of batik MSMEs